Investigating Subjectivity Criterion for Multi-video Summarization - Barbieri, Tamires Tessarolli de Souza; Goularte, Rudinei (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2020)
Currently, videos play an important role in people's every day lives and there is a continuous increase in their production and consumption. However, to make video information access a feasible task, smarter and more efficient strategies are needed in order to deal with this complex and huge data volume. In this context, automatic video summarization becomes a significant tool. This research area aims to produce a smaller version of original video, keeping its most meaningful information. Particularly for some relavant domains, like news and education, it is important a summary to be generated from a set of related videos - different videos about the same subject. In the automatic multi-video summarization field a common and essential step is to define content selection criteria. A promising approach, yet unexploited by related work, is to apply inclusion and exclusion criteria derived from human strategies. In this work, we investigate how exclusion criteria can help to keep multi-video summaries short and informative. We introduce an approach to detect subjectivity into video segments from news domain, allowing those segments to be not included into the summary. Our approach is evaluated by the means of objective measures of effectiveness. We also analyze the impact that removing such subjective segments has on multi-video summarization outputs by conducting a study with final users. Results indicate that the proposed approach is able of producing more compact summaries, keeping the relevant content for the users.